Managing effectively hotel-travel agent relationships under an exogenous crisis: Its impact on customer satisfaction - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Christodoulides, Paul (My University, 2024)
Although the business relationship between a firm and its business partners can be vulnerable under a crisis situation and lead to detrimental effects on end-customers, when this is properly managed can produce favorable customer results. The goal of this study is to examine the effects of various aspects of the hotel - travel agent working relationship on its performance under an exogenous crisis situation, and how this ultimately impacts final customer satisfaction. Drawing on the relational exchange theory, we build a conceptual model connecting the quality, functionality, and conformity of the working relationship with relational performance and its subsequent impact on the hotel’s end-customer satisfaction. The model was tested using structural equation modeling using data collected from a survey among 190 hotels in Greece during the recent Covid-19 pandemic crisis, supplemented with secondary data on customer satisfaction. The results revealed that relational performance was positively affected by all variables comprising relationship quality (i.e., trust, commitment, cooperation), all variables referring to relationship functionality (i.e., coordination, communication, closeness), and two of the variables composing relationship conformity (i.e., solidarity, adaptation). It was also shown that the resulting relational performance had a positive effect on end-customer satisfaction.